Differential Functional Connectivity Alterations of Two Subdivisions within the Right dlPFC in Parkinson's Disease - Caspers, Julian; Mathys, Christian; Hoffstaedter, Felix; Südmeyer, Martin; Cieslik, Edna C.; Rubbert, Christian; Hartmann, Christian J.; Eickhoff, Claudia R.; Reetz, Kathrin; Grefkes, Christian; Michely, Jochen; Turowski, Bernd; et al. (Frontiers in Human Neuroscience, 2017)
Patients suffering from Parkinson’s disease (PD) often show impairments in executive function (EF) like decision-making and action control. The right dorsolateral prefrontal cortex (dlPFC) has been strongly implicated in EF in healthy subjects and has repeatedly been reported to show alterations related to EF impairment in PD. Recently, two key regions for cognitive action control have been identified within the right dlPFC by co-activation based parcellation. While the posterior region is engaged in rather basal EF like stimulus integration and working memory, the anterior region has a more abstract, supervisory function. In order toTo investigate , if whether these functionally distinct subdivisions of right dlPFC are differentially affected in PD, we investigated analyzed resting-state functional connectivity (FC) in 39 PD patients and 44 age- and gender-matched healthy controls. Patients were examined both after at least 12h withdrawal of dopaminergic drugs (OFF) and under their regular dopaminergic medication (ON). We found that only the posterior right dlPFC subdivision shows FC alterations in PD, while the anterior part remains unaffected. PD-related decreased FC with posterior right dlPFC was found in the bilateral medial posterior parietal cortex (mPPC) and left dorsal premotor region (PMd) in the OFF state. In the medical ON, FC with left PMd normalized, while decoupling with bilateral mPPC remained. Furthermore, we observed increased FC between posterior right dlPFC and the bilateral dorsomedial prefrontal cortex (dmPFC) in PD in the ON state. Our findings point to differential disturbances of right dlPFC connectivity in PD, which relate to its hierarchical organization of EF processing by stronger affecting the functionally basal posterior aspect than the hierarchically higher anterior part.